Benchmarking Brexit: How the British Decision to Leave Shapes EU Public Opinion* - de Vries, Catherine (Wiley, 2017)
On 23 June 2016, by a small majority the British population voted to leave the European Union (EU). The British decision to leave shocked the political establishment in London, Brussels and beyond. Immediately after the vote, the pound fell sharply as uncertainty among investors about Britain’s economic future started to grow. Politically, the situation was not much different. Not only did Prime Minister David Cameron resign, but the referendum result unmasked deep divisions between different regions and amongst the constituent components of the United Kingdom as well as within the two major political forces in Westminster, the Conservative and Labour parties. New Prime Minister Theresa May was confronted with the daunting task of negotiating British withdrawal from the EU whilst keeping her party and country together at a time when the exact economic costs of Brexit are still highly uncertain. While the British economy weathered the vote and its immediate aftermath better than expected, long-term assessments of a post-Brexit British economy are less rosy.2 This might be at least in part the result of the Brittish government’s decision to delay the triggering of Article 50. The market response following the invoking of the article seems to suggest as such.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 10 - Reducción de las desigualdades